Acres of unrest a western story - Brand, Max (Waterville, Me. : Thorndike Press, 2007)
Injured in an accident at college, Peter Hale can longer work his father's ranch, but he has a plan to give the homestead an infusion of cash--a plan no one would expect a cripple to pull off.
90536
Keywords: Ranch life; People with disabilities -- Fiction; Large type books; Western stories